E-039 Comparison of Medical Therapy vs. Intra-Arterial Therapy for Acute Vertebrobasilar Stroke. (29th July 2016) - Raymond, S; Leslie-Mazwi, T; Rost, N; Schaefer, P; Hirsch, J; Gonzalez, R; Rabinov, J
Abstract : Introduction/purpose: We present a consecutive retrospective cohort of patients treated at an academic stroke center for acute ischemic stroke from large vessel occlusion of the vertebrobasilar circulation. We describe prognostic factors and outcomes for patients receiving medical and/or intra-arterial therapy (IAT) over a 12 year period. Materials and methods: We treated 87 patients (medical therapy N = 44 and IAT = 43) between 2004–2015 for acute posterior circulation infarct with vertebrobasilar occlusion at our institution. Patients were dichotomized by modified Rankin Score (mRS) to good outcome defined as mRS 0–2 or poor outcome defined as mRS 3–6. Multiple characteristics were compared including age, gender, NIHSS, infarct volume, posterior ASPECTS, thrombus location, hconversion and treatment modality (medical therapy or IAT). Categorical variables were compared using Chi-square statistic, and continuous variables were compared using t-test and Mann-Whitney statistics. The study was conducted with IRB approval. Results: Major etiologies of acute basilar occlusion included atrial fibrillation, PFO, vertebral artery dissection with distal embolus, and intracranial atherosclerosis (ICAD). Poor outcomes were associated with higher NIHSS, lower ASPECTS and extensive brainstem involvement on DWI. IAT patients presented with more severe deficit (NIHSS 21) compared to patients treated medically (NIHSS 14). Rates of good outcomes (mRS 0–2) were equivalent between the IAT (21/43, 49%) and medically treated cohort (21/44, 48%). When ICAD patients were excluded from analysis, results were similar with 50% of the IAT patients (18/36) and 43% of medically treated patients (15/35) having a good outcome. This time period spans major changes in endovascular techniques ranging from urokinase and wire manipulation to current devices. ADAPT or stentrievers were only uin ten cases. Conclusion: Compared to medical trials in 2015, which demonstrate clinical benefit for IAT over medical therapy for acute ischemic stroke of the anterior circulation, the posterior circulation is less well studied. Important prognostic factors for stroke due to large vessel occlusion of posterior circulation include posterior ASPECTS score and infarct volume in the brainstem. In this small retrospective study, patients treated with IAT had greater stroke severity than the medical cohort, yet they had similar rates of good functional outcome. Parameters of this retrospective analysis may be used to improve triage and treatment of patients with acute vertebrobasilar occlusion for thrombectomy using current technology. References: 1 Singer OC, Berkefeld L, Nolte CH, et al . Mechanical recanalization in basilar artery occlusion: The ENDOSTROKE Study. Ann Neurol 2015 Mar;77 (3):415–24. 2 Strbian D, Sairanen T, Silvennoinen H, et al . Thrombolysis of basilar artery occlusion: impact of baseline ischemia and time. Ann Neurol 2013 Jun;73 (6):688–94 Disclosures: S. Raymond: None. T. Leslie-Mazwi: None. N. Rost: None. P. Schaefer: None. J. Hirsch: 2; C; Medtronic. R. Gonzalez: None. J. Rabinov: None.